A Phenomenological Study of Child Neglect in a Family Entangled in Loan Sharks' Debt in Ngajum Village, Malang Regency - Rahmawati, Devira; Ahmad Ridwan; Diyah Utami (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
Child neglect in families caught up in loan shark debt is an increasingly worrying social phenomenon in Ngajum Village, Malang District. Economic pressure due to loan shark debt not only disrupts the financial stability of the family, but also has an impact on neglecting the physical and psychological needs of children. This study aims to understand parents' subjective experiences of child neglect due to the pressure of loan shark debt. This research employs a qualitative approach, utilizing Edmund Husserl's phenomenological method through in-depth interviews and participatory observation of selected informants. The results show that the burden of debt causes family dysfunction, with the main focus of parents on debt repayment, so that the needs of children are neglected. Children experience emotional uncertainty, minimal communication with parents, physical and psychological abuse, and limited fulfillment of basic needs. Furthermore, this study reveals that the experience of neglect committed by parents due to loan sharks' debts contributes to social stigmatization, internal justification for neglect, and emotional disconnection between parents and children. These findings highlight the importance of enhancing financial literacy in families to prevent its impact on child neglect. This research contributes to broadening the understanding of the impact of loan shark debt on family dynamics from a phenomenological perspective and encourages the birth of social interventions that are more empathetic and contextual.